Analysis of estuarine flood levels based on numerical modelling. The Douro river estuary case study - Venâncio, Stênio de Sousa; Pinho, José Luís; Vieira, José Manuel; Avilez-Valente, Paulo; Iglesias, Isabel (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2019)
Estuarine hydrodynamics present intermittent and complex circulation patterns. In this context, from the point of view of the coastal management associated with flood risks in riverine areas, numerical models allow predicting scenarios under specific hypotheses. This work simulates flood events occurring in the Douro river estuary recurring to numerical modelling tools. This estuary, located in the northern region of Portugal, periodically suffered severe flooding, with the associated losses and damages for the local protected landscape areas and hydraulic structures. The occurrence of these events justify the importance of a complete characterization of the areas that present risk of inundation and how they can be affected. A 2D-horizontal numerical model implemented with the Delft3D software was developed for this estuarine region including also the adjacent coastal zone. Available in-situ data were used for model calibration and validation processes. The obtained results are consistent with the in-situ measured water levels, allowing to understand the dynamics of the estuary during flood events. The robustness of the implemented numerical model allows to anticipate flood scenarios effects and associated water levels. The simulations results can then be used for sustainable management of this estuarine zone that presents high social, economic and environmental values.